2005
DOI: 10.1099/jmm.0.46071-0
|View full text |Cite
|
Sign up to set email alerts
|

Development and evaluation of a loop-mediated isothermal amplification assay for rapid detection of Mycoplasma pneumoniae

Abstract: A loop-mediated isothermal amplification (LAMP) assay for the rapid detection of Mycoplasma pneumoniae was developed and evaluated. The assay specifically amplified only M. pneumoniae sequences, and no cross-reactivity was observed for other Mycoplasma species or respiratory bacterial species. The detection limit for this assay was found to be 2 3 10 2 copies, corresponding to 2-20 colour changing units of M. pneumoniae in 1 h, as observed in a real-time turbidimeter and electrophoretic analysis. The accuracy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
49
0
4

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(55 citation statements)
references
References 18 publications
2
49
0
4
Order By: Relevance
“…Compared to a standard PCR protocol, LAMP requires a single bath at a constant temperature instead of a thermal cycler. The performances of LAMP-and PCR-based diagnostic systems, including real-time technologies (23,40), have been extensively compared. In general, LAMP was found to be either similar or superior to PCR, and more specific (e.g., 8,13,15), but a few studies proved otherwise, such as those reported by Kato et al (18), who showed that although LAMP was 10-fold more sensitive than standard PCR for the detection of the Clostridium difficile toxin B gene (tcdB), an optimized nested-PCR assay performed much better than LAMP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared to a standard PCR protocol, LAMP requires a single bath at a constant temperature instead of a thermal cycler. The performances of LAMP-and PCR-based diagnostic systems, including real-time technologies (23,40), have been extensively compared. In general, LAMP was found to be either similar or superior to PCR, and more specific (e.g., 8,13,15), but a few studies proved otherwise, such as those reported by Kato et al (18), who showed that although LAMP was 10-fold more sensitive than standard PCR for the detection of the Clostridium difficile toxin B gene (tcdB), an optimized nested-PCR assay performed much better than LAMP.…”
Section: Discussionmentioning
confidence: 99%
“…(19,44) and pathogenic fungi such as Paracoccidioides brasiliensis (7) and Ochroconis gallopava (34) have also been addressed. LAMP-based approaches have been applied to a wide range of samples, such as paraffin-embedded tissues (7), whole blood (36), nasopharyn-geal swabs (17,40), dental plaques (23), eggs (13), and potato leaf samples (32).…”
mentioning
confidence: 99%
“…The clinical samples for diagnosis are initially treated with a specifi c antibody-coated beads, and the target bacteria after reaction with their specifi c antibody are separated from other bacteria by immunomagnetic separation (IMS) [Bapanpally et al, 2014;Taguchi et al, 2007]. Loop-mediated isothermal amplifi cation (LAMP) is a sensitive, specifi c, convenient and fast nucleic acid amplifi cation technology, which obviates the need for expensive thermal cyclers used in conventional PCR [Saito et al, 2005]. The LAMP was designed with four specifi c primers for the six regions of the unique target gene using strand displacement DNA polymerase activity in addition to a nucleic acid amplifi cation activity at a constant temperature of 60-65°C [Hara- Kudo et al, 2008].…”
Section: Introductionmentioning
confidence: 99%
“…using phytoplasma-specific antibodies and ELISA-based or lateral flow devices (LFD)-based systems, fall down because of a lack of sensitivity, and whilst a phytoplasma IgG antibody based system is commercially available for few phytoplasmas (103). Recently, Fera (Food and Environment Research Agency) developed isothermal amplification assays, such as the Loop-Mediated Isothermal Amplification (LAMP) procedure for detection of several human and plant pathogens including phytoplasmas (130,140,37,154). In the method the cycling accumulates stem-loop DNAs with several inverted repeats of the target and cauliflower-like structures with multiple loops, and produces up to 10 9 copies of the target in less than 1 h at 65°C.…”
Section: Loop-mediated Isothermal Amplification Assay (Lamp)mentioning
confidence: 99%